Carrying out Research into Learning Through on line Discussion: Opportunities and Difficulties - Hammond, Michael; Wiriyapinit , Mongkolchai (Proceedings of the International Conference on Networked Learning, 2004)
This paper reports on approaches to researching on line discussion. The context is an extended study of an E business module at the University of Warwick in which the use of communication technology is pivotal. The module requires students to tackle case based activities within on line groups and gives opportunities to explore on line course materials. A study of student learning within this module was undertaken through questionnaire surveys, text analysis and interview. This paper reports on the value of these different approaches to research and highlights the value of a mixed or triangulated approach to the research of on line discussion.